1999
DOI: 10.1097/00003246-199911000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized, controlled trial to determine the effect of early enhanced enteral nutrition on clinical outcome in mechanically ventilated patients suffering head injury

Abstract: Enhanced EN appears to accelerate neurologic recovery and reduces both the incidence of major complications and postinjury inflammatory responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
260
1
12

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(276 citation statements)
references
References 31 publications
2
260
1
12
Order By: Relevance
“…Six RCTs317, 318, 319, 320, 321, 322 included in the systematic review of the JSICM guidelines were extracted. All six RCTs reported on mortality rate, three reported on infection frequency, two RCTs reported on the duration of ventilation, the length of ICU stay, and length of hospital stay; four RCTs reported on ventilator‐associated pneumonia (VAP), and two RCTs reported on the frequency of continuous renal replacement therapy (CRRT) use.…”
Section: Cq13: Nutritionmentioning
confidence: 99%
“…Six RCTs317, 318, 319, 320, 321, 322 included in the systematic review of the JSICM guidelines were extracted. All six RCTs reported on mortality rate, three reported on infection frequency, two RCTs reported on the duration of ventilation, the length of ICU stay, and length of hospital stay; four RCTs reported on ventilator‐associated pneumonia (VAP), and two RCTs reported on the frequency of continuous renal replacement therapy (CRRT) use.…”
Section: Cq13: Nutritionmentioning
confidence: 99%
“…Schilling et al (1996) did not find significant differences in phagocytic activity of monocytes, activated surface antigen HLA-DR, and CRP levels between a control formula and a formula supplemented with arginine, omega 3 fatty acids and nucleotides; however both formulas were better than a low energy=low fat intravenous solution. However, Taylor et al (1999) showed a decrease in CRP levels in head injury patients treated with an enhanced formula without differences in other biochemical parameters. These results were confirmed by Weimann et al (1998) in a group of multiple organ failure patients.…”
Section: Discussionmentioning
confidence: 80%
“…recommend the advancement of feeding toward the target over the 48 -72 h after the start of EEN [1], and the Canadian Clinical Practice Guidelines (CCPG) recommend starting at target feeding rate when initiating EN in critically ill patients [2]. Several studies support each of these recommendations [9]- [14]. Taylor feeding in patients with a BMI of approximately 28 kg/m 2 in the first 7 days in an ICU [14], and found that the normocaloric group had a lower incidence of nosocomial infection than the hypocaloric group.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, many of these studies were conducted in Western countries in patients with normal weight or excessive body weight (BW). For underweight patients with limited nutritional reserves, advancing feeding too slowly might result in undernutrition or poor clinical outcomes [9]- [14]. We previously reported that reduced energy intake during the first week of ICU admission was associated with a reduced duration of mechanical ventilation (MV) in critically ill, underweight patients [15].…”
Section: Introductionmentioning
confidence: 99%